Contextual liberalism: the ordoliberal approach to private vices and public benefits - Roland Fritz; Nils Goldschmidt; Matthias Störring (Public Choice, 2021)
This article highlights the various sources that shaped the genesis of ordoliberalism. In the wake of the emerging project of neoliberalism, ordoliberals created a theory that contains a bundle of claims, which constitute the attempt to merge liberalism and its contextual embedding into a social philosophy that meets the requirements of both—economy and society. They were concerned with a new and properly interpreted liberalism. Not because they did not share the basic assumption of classical liberalism that individual self-interested action is the necessary driving force in advancing economic and social progress, but because they realized that individual action requires an embedding into a social and moral order to deliver public benefits. This insight proves to be the significant difference between ordoliberals of neoliberal facon and the exponents of classical liberalism: namely that the market economy operates based on prerequisites which it cannot itself guarantee. Regarding their very own historical context, this must be seen in light of their concern for the reconstruction of Western societies after the end of the totalitarian Nazi regime. The purpose of ordoliberalism has always been the "consciously shaped" economic order which manifests itself as humane and as functional. Moreover, if one understands ordoliberalism as contextual liberalism, it can also be significant for today's discourse. In order to achieve this aspiration, ordoliberalism adopts a contextual approach. In particular, linkages can be drawn here to Constitutional Political Economy, and the interaction of these perspectives offer promising benefits for both "thinking-in-orders" traditions.
Keywords: B15; B31; P48; 330; Ordoliberalism; Neoliberalism; German historical school; Constitutional political economy; Economic methodology